2016
DOI: 10.1007/s00167-016-4087-0
|View full text |Cite|
|
Sign up to set email alerts
|

An in vitro analysis of medial structures and a medial soft tissue reconstruction in a constrained condylar total knee arthroplasty

Abstract: PurposeThe aim of this study was to quantify the medial soft tissue contributions to stability following constrained condylar (CC) total knee arthroplasty (TKA) and determine whether a medial reconstruction could restore stability to a soft tissue-deficient, CC-TKA knee.MethodsEight cadaveric knees were mounted in a robotic system and tested at 0°, 30°, 60°, and 90° of flexion with ±50 N anterior–posterior force, ±8 Nm varus–valgus, and ±5 Nm internal–external torque. The deep and superficial medial collateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In this study, a valgus torque of 10Nm was used, which might be insufficient to produce a valgus laxity in extension. However, multiple previous studies have demonstrated valgus laxity using a valgus torque of 10Nm or less [2,5,7,13].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, a valgus torque of 10Nm was used, which might be insufficient to produce a valgus laxity in extension. However, multiple previous studies have demonstrated valgus laxity using a valgus torque of 10Nm or less [2,5,7,13].…”
Section: Discussionmentioning
confidence: 96%
“…A previous study investigating the same soft-tissues with an older design of constrained condylar implant (DePuy Synthes Rotating-Platform TC3) and the same loading conditions found an average of 72% across flexion angles ( p = 0.138 by unpaired 2-way t test, n.s.) [ 2 ]. There were similar findings under ± 50 N AP loads: with anterior drawer the medial soft-tissues resisted 51% for both the Attune and the TC3, and with posterior drawer 17% and 21% with the Attune and TC3 respectively ( p = 0.140, n.s.).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, good stability cannot be achieved without the laxity of MCL. 13 However, extensive loosening of the lateral structure can destroy the rotational stability of knee joint under knee flexion, concentrate the stress of polyethylene liner and increase the wear. At the same time, the radiolucent lines may appear earlier on the tibial plateau, which are visible in 70% of the patients.…”
Section: Discussionmentioning
confidence: 99%